Anti-Parkinsonian effect of Mucuna pruriens and Ursolic acid on GSK3β/Calcium signaling in neuroprotection against Rotenone-induced Parkinsonism - Walia Zahra; Hareram Birla; Saumitra Sen Singh; Aaina Singh Rathore; Hagera Dilnashin; Richa Singh; Priyanka Kumari Keshri; Shekhar Singh; Surya Pratap Singh (Elsevier, 2022)
Background: Exposure of environmental toxin is linked to the onset of Parkinson's disease (PD), especially in majority of sporadic cases. One of such toxins, namely Rotenone has been widely investigated to produce the Parkinsonian model in laboratories. The toxin causes the death of the dopaminergic neurons, aggregation of α-Synuclein, oxidative stress, neuroinflammation and initiate other pathways leading to PD pathogenesis. Glycogen synthase kinase-3 (GSK-3) is a pleiotropic serine/threonine protein kinase found in eukaryotes. One of the two isoforms of the enzyme; GSK-3β plays an important role in regulating the pathogenesis of neurodegenerative diseases, including PD. Whereas, Calcium (Ca2+) is found to regulate important cellular activities in all eukaryotic cells. However, an increased Ca2+ concentration is seen during ageing and the progression of neurodegenerative diseases. Thus, maintaining the Ca2+ homoeostasis is very crucial for proper cell function. Methodology: Hence, behavioural tests were performed to assess the motor abnormalities; immunohistochemical and western blot analyses to identify the alteration in the protein expression; and mitochondrial complexes and antioxidants assay to detect the extent of mitochondrial dysfunction in Rotenone-induced Parkinsonian mouse model. Alternatively, the effect of Mucuna pruriens (Mp) and Ursolic acid (UA) in the PD mouse model was also observed. Results: Increased Ca2+level, and activation of GSK-3β was observed in the Rotenone-intoxicated mouse model of PD. The extract of Mp and UA, on the other hand shows neuroprotection through their anti-oxidative and anti-inflammatory properties. However, their role in maintaining the Ca2+ level and GSK-3β signaling is not yet observed in PD. So, our study deals with the downregulated activity of GSK-3β and Ca2+ level upon the administration of Mp extract and UA, thereby providing neuroprotection to the PD mouse model. Conclusion: Thus, this study deals to explore further the neuroprotective activity of Mp and UA through GSK-3β/Calcium signaling by ameliorating mitochondrial dysfunction mediated apoptosis and inhibiting the overexpression of α-Synuclein in Rotenone-induced PD mouse model.